PCR-DGGE: a new technique in the world of microbiology - arvin tavakoli (بیولوژی کاربردی, 2017)
PCR-DGGE is one of the newest molecular methods. This technique separates co-size DNA fragments based on sequence differences and was originally devised to discover DNA polymorphism. PCR-DGGE uses in different fields of microbiology Such as medical microbiology, food microbiology and industrial microbiology. In this method, after DNA extraction from the specimen, DNA is amplified by universal primers through PCR. Subsequently, the PCR is loaded on the DGGE gel containing denaturing gradient of urea and formamide and the electrophoresis is performed. The DGGE separates the DNA fragments that belong to different bacteria, which can be used for further analysis. Despite of some limitation such as length limit of considered DNA fragment, the PCR-DGGE technique can be used as a fast and efficient technique for many purposes in microbiology. In this study, following the introducing of PCR-DGGE method, we are going to investigate the advantages and limitations of this technique in microbiological research.